PERAN PEMANGKU ADAT TERHADAP PENGAMBILAN KEPUTUSAN KELOMPOK (FENEMENOLOGI PADA MASYARAKAT DI DESA SUNGAI BATANG, KABUPATEN AGAM,SUMATERA BARAT) - Reni Novia (Interpretasi: Communication & Public Relations, 2021)
This study examines the role of traditional stakeholders in group decision-making, with a phenomenological study of the community in Sungai Batang Village, Agam Regency, West Sumatra. The formulation of the problem in this study is, how is the role of traditional stakeholders in group decision making (phenomenology of the community in Sungai Batang Village, Agam Regency, West Sumatra). The purpose of this study was to determine the role of traditional stakeholders in group decision making (phenomenology in the community in Sungai Batang Village, Agam Regency, West Sumatra. The method in this study was qualitative phenomenology, the object of research was the community in Sungai Batang Village, Tanjung Raya District, Religious District. , West Sumatra. The validity of the data used triangulation of sources and researchers, by comparing and rechecking the results of interviews that researchers conducted with sources. Research results in this study include: (1) Decision making in the community in Sungai Batang has a series of alternatives that are decided rationally or with common sense by customary stakeholders; (2) In the process of making customary decisions in Sungai Batang, this process goes through stages that are not immediately decided, but require a series of communication with customary stakeholders.